Determination of volatile marker compounds of common coffee roast defects. (15th November 2016) - Yang, Ni; Liu, Chujiao; Liu, Xingkun; Degn, Tina Kreuzfeldt; Munchow, Morten; Fisk, Ian
Highlights: Coffee was roasted and five typical roasted defects were replicated. Light roast defect had increased indole. Scorched roast defect had increased 4-ethyl-2-methoxyphenol. Dark and baked roast defect had increased phenol and maltol respectively. Underdeveloped roast defect had increased 2, 5-dimethylfuran. Abstract: Coffee beans from the same origin were roasted using six time-temperature profiles, in order to identify volatile aroma compounds associated with five common roast coffee defects (light, scorched, dark, baked and underdeveloped). Thirty-seven volatile aroma compounds were selected on the basis that they had previously been identified as potent odorants of coffee and were also identified in all coffee brew preparations; the relative abundance of these aroma compounds was then evaluated using gas chromatography mass spectrometry (GC–MS) with headspace solid phase micro extraction. Some of the 37 key aroma compounds were significantly changed in each coffee roast defect and changes in one marker compound was chosen for each defect type, that is, indole for light defect, 4-ethyl-2-methoxyphenol for scorched defect, phenol for dark defect, maltol for baked defect and 2, 5-dimethylfuran for underdeveloped defect. The association of specific changes in aroma profiles for different roast defects has not been shown previously and could be incorporated into screening tools to enable the coffee industry quickly identify if roast defects occur during production.